2020
DOI: 10.5217/ir.2019.00120
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological role of Atg5 in human ulcerative colitis

Abstract: Background/Aims: Ulcerative colitis (UC), along with Crohn’s disease, is one of the main types of inflammatory bowel disease (IBD). On the other hand, deregulated autophagy is involved in many chronic diseases, including IBD. In this study, we aimed to investigate the role of Atg5 and microRNA-181a (miR-181a) in the pathophysiology of UC. Methods: Colon biopsy, stool, and blood samples of 6 men and 9 women were confirmed for UC. Also, 13 men and 17 women were selected as healthy control (HC). Enzyme-linked imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In addition, our group for the first time reported the association between lower serum levels of ATG7 and human UC (Lankarani et al, 2017). Also, we found a significant increased level of fecal ATG5 in UC patients (Ardali et al, 2020). So far, the importance of ATG10 in human UC has not been evaluated yet.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, our group for the first time reported the association between lower serum levels of ATG7 and human UC (Lankarani et al, 2017). Also, we found a significant increased level of fecal ATG5 in UC patients (Ardali et al, 2020). So far, the importance of ATG10 in human UC has not been evaluated yet.…”
Section: Discussionmentioning
confidence: 65%
“…26 Ardali et al found that UC patients had higher contents of ATG5 in both stool and serum compared with healthy controls. 27 ATG9 abundantly exists in cytoplasmic vesicles that are assembled into the preautophagosomal structure in response to environmental stimuli and eventually incorporated into the autophagosomal outer membrane. 28 Overexpression of miR-29a inhibited the autophagy of intestinal epithelial cells in UC by decreasing the expression of ATG9A.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study suggested that the genetic susceptibility of TNFSF15 to CD may be partially confounded by an increase in Prevotella 46 . An Iranian study reported a significantly higher level of fecal ATG5, which is a protein required for autophagosome formation, in patients with UC and suggested that ATG5 protein found in stools could be a potential diagnostic biomarker for the diagnosis of UC 47 . One Korean study identified hypermethylated promoters of tumor suppressor genes (TSGs) in patients with CD, suggesting they may be candidate noninvasive diagnostic markers of IBD 48 …”
Section: Disease Susceptibility Genes and Diagnostic Biomarkers For Ibdmentioning
confidence: 99%